A palynological systematic nomenclature - van der Hammen, Thomas (Boletín Geológico, 1956)
The present article deaIs with a new artificial palynological nomenclature. The genera and generic names of pollengrains are based on the pollen-types of IVERSEN & TROELS-SMITH (1950) and the subgenera and sub-generic names on the sculpture-types of the same authors. The main part of the theoretically possible genera and some of the sub-genera are described with their type species. For spores a similar system is proposed, but the genera are n0t described here with their type-species, as many spore-genera are established already from the Paleozoic.